KODE KEHORMATAN KEPRAMUKAAN - Armeni Maulina Siregar; ,Fadhilatul Difla; Tahsa Rafelya Diningtias (CV. Arsy Persada Quality, 2024)
This research aims to find out the scout code of honor. This research uses descriptive qualitative research, documentation methods. The research results of the Scout Honor Code in the form of moral provisions called Darma are a tool for the progressive educational process itself to develop noble character, an effort to provide practical practice that encourages students to determine, appreciate, adhere to the value system of the society in which they live and are members; the foundation of the Scout Movement to achieve educational goals through Scouting whose activities encourage Scouts to be one with society, to be democratic, to respect each other, to have a sense of unity and mutual cooperation; code of ethics for Scout organizations and units